VANCOMYCIN RESISTANT ENTEROCOCCI AT A TERTIARY CARE HOSPITAL IN NORTHERN INDIA - RAJKUMAR KALYAN; MASTAN SINGH; JYOTSNA AGARWAL (International Journal of Pharma and Bio Sciences, 2013)
Resistant enterococci is a real threat and continuous surveillance is necessary to monitor its magnitude. Risk factors and phenotypic characteristics of VRE isolated in Gandhi memorial and associated hospital, K.G’s .Medical University Lucknow a tertiary care setup. Method: Enterococci were isolated from various clinical specimens and identified phenotypically, vancomycin resistance pattern using both disc diffusion and minimum inhibitory concentration methods. High level resistance (HLR) to streptomycin, kanamycin, and gentamicin was determined and beta lactamase production was detected using three methods: Acidometric, iodometric and chromogenic beta lactams. Results: Amongst 86 enterococci isolated 4 isolates were resistant to vancomycin but sensitive to teicoplanin, 34 were found to have high level resistance (HLR) to some aminoglycosides. HLR was more to kanamycin than streptomycin and gentamicin. Only 1 isolate produced beta lactamase. Conclusion: Frequency of isolation of VRE was not very high in our setting and prolonged hospital stay was the common risk factor . Frequent occurrence of HLR to kanamycin makes amikacin a poor choice to achieve synergistic therapy with cell wall active agent.